Nearly universal, but somewhat distinct: The feminization of poverty in affluent Western democracies, 1969-2000 - David Brady; Denise Kall (Luxembourg Income Study (LIS), 2007)
Our study extends research on the feminization of poverty by analyzing the variation in women's, men's and feminized poverty across affluent democracies from 1969 to 2000. Specifically, we address three issues. First, we provide more recent estimates of adult women's and men's poverty and the ratio of women's to men's poverty with two different poverty measures. We suggest that by incorporating the elderly, the feminization of poverty may be greater than previously estimated. The feminization of poverty is nearly universal across affluent Western democracies 1969-2000. Second, we show that women's, men's and overall poverty are highly correlated, but the feminization of poverty diverges as a distinct social problem. Third, we find that women's, men's and overall poverty share several correlates, particularly the welfare state, though some differences exist. At the same time, several of our findings differ with past research. The feminization of poverty is only influenced by social security transfers, single motherhood, and the sex ratios of the elderly and labor force participation. While power resources theory probably best explains women's, men's and overall poverty, structural theory may best explain the feminization of poverty. We conclude by discussing how analyses of the feminization of poverty contribute to debates on poverty and gender inequality.
Keywords: 330; Armut; Geschlecht; Frauen; Männer; Schätzung; Welt